2020
DOI: 10.32854/agrop.vi.1677
|View full text |Cite
|
Sign up to set email alerts
|

Características bromatológicas y fermentativas in vitro de complementos con Enterolobium cyclocarpum (Jacq.) Griseb y cáscara de Cucurbita argyrosperma Huber

Abstract: Objetivo: Determinar las características bromatológicas y fermentativas in vitro de complementos elaborados con harina de vaina de parota, cascara y pulpa de calabaza. Metodología: Los complementos evaluados fueron C1 = 50% harina de cascara con pulpa de calabaza y 50% de harina de vaina de parota; C2 = 60% harina de cascara con pulpa de calabaza y 40% de harina de vaina de parota; C3 = 70% harina de cascara con pulpa de calabaza y 30% de harina de vaina de parota. En los complementos se determinó materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…They reported a pH of 6.69 in the culture media after the in vitro ruminal anaerobic fermentation of silages made of Lollium perenne grass. Furthermore, the pH in this study is similar to that reported in complements prepared with 70% PSP flour and 30% of parota pod flour (Rojas-García et al, 2020). After 72 h of in vitro fermentation, the total bacteria count was not significantly different between the ingredients used to prepare the silages.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…They reported a pH of 6.69 in the culture media after the in vitro ruminal anaerobic fermentation of silages made of Lollium perenne grass. Furthermore, the pH in this study is similar to that reported in complements prepared with 70% PSP flour and 30% of parota pod flour (Rojas-García et al, 2020). After 72 h of in vitro fermentation, the total bacteria count was not significantly different between the ingredients used to prepare the silages.…”
Section: Resultssupporting
confidence: 84%
“…The pH of the biodigester's culture medium was not significantly different (p0.05) between silages or between the unprocessed ingredients (Table 3), with an average pH of 6.78. These values remain between the normal range (6.0 to 7.0) of the ruminal microbiota (Kolver and de Veth, 2002), particularly of cellulolytic bacteria, since their activity is not inhibited (Rojas-García et al, 2020). However, pH values lower than 6.0 inhibit their activity (Ley de Coss et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
“…Insurgente and Tanzania had the highest k values at 30 d, Llanero at 45 d, and Bermuda at 60 d (p ≤ 0.05) (Table 5). b indicates the fermentation rate and can be assumed indirectly as the exponential growth rate of the inoculum (Rojas-García et al, 2020), because the rate of increase of bacteria in a time is proportional to the product of their fermentation, in this case, biogas. At 30 days, Bermuda, Estrella, and Pangola had the highest b values; at 45 days, Pará had the highest b; and at 60 days, Estrella had the lowest b (p ≤ 0.05) (Table 5).…”
Section: Resultsmentioning
confidence: 99%